The Influence of Brand Ambassador, Digital Marketing and Tagline on Tokopedia's Brand Awareness in Jakarta City - Miranda Maharani Tobing; Siti Ning Farida (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research was conducted to understand the influence of brand ambassador, digital marketing, and tagline on brand awareness of Tokopedia in Jakarta. The increasing sophistication of technology has led to changes in consumer behavior, particularly in the context of online shopping through marketplaces. The study aimed to investigate the impact of brand ambassador, digital marketing, and tagline on brand awareness. The research design involved a quantitative approach, utilizing regression analysis. The participants were consumers of Tokopedia in Jakarta. The results indicated that brand ambassador, digital marketing, and tagline have a positive influence on brand awareness. Simultaneously, all three variables significantly affect brand awareness. However, when analyzed individually, it was found that brand ambassador and tagline do not have a significant impact, while digital marketing does.